Virulence Factors of Proteus Mirabilis Isolated From Patients Otitis Media in Baquba And it’s Peripheries - A. Al-Duliami , Abbas; G. Nauman , Nadhum; SH. Hasan , Abdul-Razak; H. Al-Azawi , Zianab (Diyala Journal of Medicine, 2019)
Background: Otitis media is one of the well known diseases that infect children and adult. The severity of infection caused by the members of the genus Proteus depends mainly on the availability of virulence and pathogenicity factors. Objectives: to detect and evaluate the presence of virulence factors in local isolates of Proteus species causing otitis media. Patients and methods: Two hundred and seventy ear swabs were collected from patients with otitis media attended Baquba General Hospital for the period from. Swab were cultured on blood, MacConkey and chocolate agar plates and incubated at 370C for 24 hrs. Chocolate agar plates were incubated under 10% CO2 (Candle jar). Suspected colonies of proteus species were isolated and subcultured on MacConkey agar. The identification of bacterial isolate was performed according to the standard biological and biochemical methods. Virulence factors including; urease, β-Lactamase and extended spectrum β-Lactamase (ESBLs), Human and ovine blood agglutination and adhesion to epithelial cells, hemolysin, esterase and proteolytic enzymes were detected following standard biochemical methods. Biofilm formation was detected by enzyme-linked immunosorbant assay. Results: Out of 270 ear swabs, 240 (88.9%) were positive for bacterial growth and of these 35 (12.9%) were identified as of Proteus species. Following the standard biochemical and enzymes tests, 7 (2.6%) was found to be Proteus vulgaris and 28 (10.4%) were Protues mirabilis. Conclusion: P.mirabilis appeared as one of the causative agent of otitis media in patients from Diyala province, and most isolates have multiple virulence factors that may increase their infectivity and worsen the clinical picture of the disease.